Integrated Analysis of Interglacial Climate Dynamics (INTERDYNAMIC) - Schulz, Michael (SpringerBriefs in Earth System Sciences, 2015)
DFG Priority Research Program „Integrated analysis of interglacial climate dynamics” (INTERDYNAMIC) -- Comparison of Climate and Carbon Cycle Dynamics during Late Quaternary Interglacials -- Global Synthesis of Sea-Surface Temperature Trends During Marine Isotope Stage 11 -- Climate Sensitivity During and Between Interglacials -- What Ends an Interglacial? Feedbacks Between Tropical Rainfall, Atlantic Climate and Ice Sheets During the Last Interglacial -- Evaluation of Eemian and Holocene Climate Trends: Combining Marine Archives with Climate Modelling -- Holocene Environmental Variability in the Arctic Gateway -- Detecting Holocene Changes in the Atlantic Meridional Overturning Circulation: Integration of Proxy Data and Climate Simulations -- Phase-shift Between Surface Ocean Warming, Evaporation and Changes of Continental Ice Volume During Termination I Observed at Tropical Ocean Sediment Cores -- Loop Current Variability – its Relation to Meridional Overturning Circulation and the Impact of Mississippi Discharge -- Hydroclimatic Variability in the Panama Bight Region During Termination 1 and the Holocene -- Control of Seasonality and Interannual to Centennial Climate Variability in the Caribbean During the Holocene – Combining Coral Records, Stalagmite Records and Climate Models -- The Southern Westerlies During the Holocene: Paleoenvironmental Reconstructions from Chilean Lake, Fjord, and Ocean Margin Sediments Combined with Climate Modeling -- Mineral Dust Variability in Antarctic Ice for Different Climate Conditions -- Model-data Synthesis of Monsoon Amplitudes for the Holocene and Eemian -- Vegetation, Climate, Man - Holocene Variability in Monsoonal Central Asia -- Global Land Use and Technological Evolution Simulations to Quantify Interactions Between Climate and Pre-industrial Cultures -- North-west African Hydrologic Changes in the Holocene: a Combined Isotopic Data and Model Approach -- Holocene Climate Dynamics, Biogeochemical Cycles and Ecosystem Variability in the Eastern Mediterranean Sea -- Environmental and Climate Dynamics During the last two Glacial Terminations and Interglacials in the Black Sea/Northern Anatolian Region -- Seasonal Reconstruction of Summer Precipitation Variability and Dating of Flood Events for the Millennium Between 3250 to 2250 Years BC for the Main Region, Southern Germany -- Precipitation in the Past Millennium in Europe – Extension to Roman Times.